2021
DOI: 10.1021/acs.energyfuels.1c01924
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Review on the Advances in the Kinetic Understanding of the Combustion of Linear and Cyclic Oxymethylene Ethers

Abstract: Oxymethylene ethers are valuable candidate e-fuels and, therefore, represent an important asset in the current energy transition. As such, the interest into predicting their combustion properties has grown significantly over the past decade. A detailed review of the existing kinetic studies of their combustion is presented, highlighting that the major part of the fundamental studies has been dedicated to dimethoxymethane (or OME 1 ). This molecule has served as a model molecule to elaborate rate rules toward p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 114 publications
(352 reference statements)
0
17
0
Order By: Relevance
“…13–15 The smallest OME homologue, dimethoxymethane (DMM ≡ OME-1; where n in OME- n denotes the number of CH 2 O units in the CH 3 O(CH 2 O) n CH 3 backbone), plays a particular role because, besides representing a fuel additive in itself, 13 it can also serve as a model compound for the development of combustion mechanisms for higher OMEs. 6…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13–15 The smallest OME homologue, dimethoxymethane (DMM ≡ OME-1; where n in OME- n denotes the number of CH 2 O units in the CH 3 O(CH 2 O) n CH 3 backbone), plays a particular role because, besides representing a fuel additive in itself, 13 it can also serve as a model compound for the development of combustion mechanisms for higher OMEs. 6…”
Section: Introductionmentioning
confidence: 99%
“…ref. 6). These compounds are discussed as additives or replacements for conventional diesel fuel [7][8][9] because they possess diesel-compatible properties 7,8 and may be produced sustainably.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Westbrook et al provided an overview of detailed kinetic models, explaining how the combustion chemistry of biofuels (alcohols, aromatic oxygenates, alkyl esters, and cyclic ethers) differs from that of alkanes. The review of Fenard and Vanhove focused on a newly considered class of biofuels, oxymethylene ethers. Three more review papers discuss the use of biofuels in applied combustion processes.…”
Section: Review Papersmentioning
confidence: 99%
“…Oxymethylene ethers (OMEs), CH 3 O(CH 2 O) n CH 3 , also known as polyoxymethylene dimethyl ethers (PODEs or DMMs), are promising fuel candidates and are currently being investigated for self-ignition engine applications. They can be produced by renewable energy sources [1] yielding a neutral greenhouse gas balance. Recent studies have shown that OME fuels, pure or in blends, can significantly reduce carbon monoxide (CO), unburned hydrocarbons, and soot particles, e.g., [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%